Hypertryptasemia and Mast Cell-Related Disorders in Severe Osteoporotic Patients. (22nd October 2020) - Carosi, Giulia; Guabello, Gregorio; Longhi, Matteo; Grifoni, Federica; Passeri, Elena; Corbetta, Sabrina
Abstract : Purpose . Systemic mastocytosis (SM) is characterized by a clonal proliferation of neoplastic mast cells (MCs) in one or more extracutaneous organs including the bone marrow (BM). SM is often associated with osteoporosis (OP) and fractures. Hypertryptasemia usually occurs in SM. We investigated the prevalence of hypertryptasemia in a series of severe osteoporotic patients, the performance of the tryptase test in diagnosing SM in these patients, and their bone features. Methods . The medical records of 232 patients (168 females and 64 males) with a diagnosis of OP (50.4% with fractures) and a serum tryptase assessment were reviewed. BM assessment was performed in a subset of hypertryptasemic patients; clinical, biochemical, and radiographic data were collected. Results . Hypertryptasemia was detected in 33 patients. BM assessment (n = 16 ) was normal in 8 hypertryptasemic patients, while BM criteria for the diagnosis of SM were met in 3 patients, MC alterations were detected in 4 patients, and one patient presented a polycythemia vera. Serum tryptase levels were higher than 11.4 ng/ml in all patients with BM alterations. The best cut-off of tryptase level related to BM alterations was 17.9 ng/ml, with a sensibility and sensitivity of 75% (AUC = 0.797 and P = 0.015 by ROC analysis). All osteoporotic patients with hypertryptasemia experienced at least one vertebral fracture associated with a severe reduction of the lumbar bone mineral density. Conclusions . The prevalence of MC-related disorders in severe OP was 3.0%, accounting for the 7.4% of the secondary causes of OP. MC-related disorders may be involved in bone fragility and assessment of serum tryptase is useful to detect MC-related disorders.